A REVIEW OF CHALLANGES IN EFFICIENT UNDERWATER ACOUSTIC COMMINICATION - Yanushevskyi, Anton; Oleksii (Science-based technologies, 2025)
The article investigates the current state, technological solutions, and pressing issues of digital underwater acoustic communication (UAC), which is gaining increasing importance due to the development of marine resource extraction, the use of autonomous and remotely operated underwater vehicles, underwater drones, monitoring systems, and the construction of the "underwater Internet of Things." The introductory part of the article analyzes modern underwater communication methods — electromagnetic, optical, and acoustic — and highlights their limitations: electromagnetic communication underwater is limited to about 10 meters due to strong attenuation; optical communication has narrow directivity and is constrained by water transparency, typically reaching up to 100 meters; whereas acoustic communication remains the only suitable and universal means of communication over distances ranging from hundreds of meters to tens of kilometers. The main part of the article focuses on the characteristics of the acoustic channel in shallow water areas (up to 200 m depth), which are particularly important considering industrial and security activities. Issues such as multipath propagation, Doppler effects, geometric and energy range limitations, and factors restricting data transmission rates are discussed. A comparison of the efficiency of different underwater acoustic communication methods is provided. The conclusions emphasize that over recent decades underwater acoustic communication technologies have achieved data transmission rates up to 48 kbps at distances around 2 km with spectral efficiency up to 4 bits/s/Hz. Improvements in spectral efficiency have been achieved through the implementation of modern technologies such as OFDM, MIMO, and high-order modulation schemes (8-PSK, 16-QAM). At the same time, the limited frequency resource and complex underwater environment restricts further growth in data transmission speeds. The authors identify key challenges for underwater acoustic communication — multipath propagation, Doppler shifts, and spectral spreading — which complicate the stability and reliability of communication. Directions for further research are proposed, including detail analysis of Doppler spreading features, the use of spatially separated antennas for small size underwater vehicles, synthesized beamforming patterns, and adaptive modulation and coding to maximize data rate and communication quality in complex and varying underwater environmental conditions, as well as the use of high-frequency bands to increase system throughput. The practical value of the work lies in the in-depth analysis of existing solutions, identifying their advantages and disadvantages, and forming recommendations to enhance the efficiency and reliability of UAC systems in changing underwater environments. The article also highlights the problem of the lack of industry standardization (except for the JANUS protocol), which complicates interoperability among heterogeneous systems, especially in coastal zones with numerous users. The article offers a classification of underwater object interaction scenarios, provides a comparative analysis of environmental impacts on UAC systems, and outlines promising directions for further development of effective and reliable underwater acoustic communication systems.